Collaborative Manufacturing Network For Small And Medium Manufacturing Enterprises - Olivia M. de Fretes (Industrial Engineering Study Program, Pattimura University, 2010)
Due to the increased exposure to competition through globalisation and free trade agreements, leading manufacturers are continuously challenged to provide high quality products at similar prices that low cost countries offer. Small and Medium Manufacturing Enterprises (SMMEs) face the same pressures as large companies, but often do not have adequate resources to remain competitive and grow. Therefore, SMMEs need to innovate and find new ways to overcome these challenges. Collaborative Manufacturing Network (CMN) promises flexibility and competitive capability, particularly for SMMEs. This paper analyses the issues, challenges and concerns faced by SMMEs in forming a CMN. Further, it explores the impacts on manufacturing industries due to the emergence of CMNs, particularly on SMMEs, since CMN challenges current business models and existing concepts.